Measurement and Analysis of Metal Element Contents in Lithium Battery Separator by ICP-OES - Yang1, Li; Xi1, Guoxi; Lou2, Tianjun; Xu2, Guangri (Asian Journal of Chemistry, 2014)
This work presents a quantitative method for determining metal contents by inductively coupled plasma optical emission spectrometer (ICP-OES) in lithium battery separator. For comparison, common drying ash and microwave digestion methods were also studied. The parameters of microwave digestion and ICP-OES were optimized, the accuracy and precision of methods was confirmed by spike and recovery experiments. Concentrations of zinc, iron, magnesium, calcium, copper, sodium, manganese, lead and cadmium were measured. The results indicated that the order of the levels of metal element in the two samples was Ca > Na > Mg > Fe > Mn, Pb, Cr in lithium battery separator, the contents of Ca and Na were the highest, Mg and Fe were the second, Cu and Zn contents were the lowest.